2018
DOI: 10.1101/501833
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blurred molecular epidemiological lines between the two dominant methicillin-resistant Staphylococcus aureus clones

Abstract: 25Background 26 Methicillin-resistant Staphylococcus aureus (MRSA) causes life-threatening infections in 27 both community and hospital settings and is a leading cause of healthcare-associated 28 infections (HAIs). We sought to describe the molecular epidemiological landscape of 29 patients with MRSA bloodstream infections (BSIs) at an urban medical center by 30 evaluating the clinical characteristics associated with the two dominant endemic clones. 31 Methods 32Comprehensive clinical data extraction from t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…The other four strains (PB 043-043, C24, PB 027-133, and PB 017-037) were selected from a larger screen of NaHCO 3 -responsive MRSA ( 12 ) based on their oxacillin and cefazolin MICs in the presence/absence of NaHCO 3 and their clonal complex (CC) types. The CC types of 7/8 isolates represent genotypes in current widespread clinical circulation (i.e., CC types 5 and 8) (see Table S1 in the supplemental material) ( 42 ). MRSA 11/11, MW2, PB 043-043, C24, BMC1001, PB 027-133, and PB 017-037 are all β-lactamase positive; COL is naturally β-lactamase negative.…”
Section: Methodsmentioning
confidence: 99%
“…The other four strains (PB 043-043, C24, PB 027-133, and PB 017-037) were selected from a larger screen of NaHCO 3 -responsive MRSA ( 12 ) based on their oxacillin and cefazolin MICs in the presence/absence of NaHCO 3 and their clonal complex (CC) types. The CC types of 7/8 isolates represent genotypes in current widespread clinical circulation (i.e., CC types 5 and 8) (see Table S1 in the supplemental material) ( 42 ). MRSA 11/11, MW2, PB 043-043, C24, BMC1001, PB 027-133, and PB 017-037 are all β-lactamase positive; COL is naturally β-lactamase negative.…”
Section: Methodsmentioning
confidence: 99%
“…Variables were analyzed initially in a univariate logistic regression model. Variables p ≤0.2 were then placed into a stepwise multivariate logistic regression model (Dupper et al 2019) . An additional in-depth chart review was performed for subjects identified as being involved in transmission events.…”
Section: Case Reviewmentioning
confidence: 99%